Design of Indonesian Sentence Grammar Checking Software Using Left Corner Parser - Nadeak, Berto; Sinaga, Sony Bahagia (Devitara Innovations, 2025)
Grammar checking is an important component of Natural Language Processing (NLP), particularly for improving the quality of written communication. This article discusses the design of grammar-checking software for Indonesian sentences using the Left Corner Parser method. The Left Corner Parser is a syntactic parsing method that combines the advantages of top-down and bottom-up parsing, making it efficient in recognizing sentence structures. This study includes the stages of data collection, the design of Indonesian grammatical rules, the implementation of the parser, and the evaluation of checking accuracy. The results show that the software can effectively detect sentence structure errors in various types of sentences, from simple to complex. With further development, this tool has the potential to be applied in educational tools and automatic text editing applications.